Penguatan Karakter Siswa melalui Pendekatan Kontekstual dalam Studi Islam - Jumrianah, Jumrianah (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
Islamic studies are often faced with the challenge of a lack of relevance between teaching materials and the reality of students' lives. This has an impact on the low understanding and application of Islamic values ​​in everyday life. The contextual approach is present as a strategic solution to connect Islamic concepts with the concrete experiences of students. This study aims to describe the implementation of the contextual approach in Islamic Studies and analyze its contribution to strengthening student character at SMA Al Munawwir Sangatta Selatan. The research approach used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The data analysis uses the interactive model of Milles, Huberan & Saldana, namely data condensation, data display, and data verification. The results of the study show that the contextual approach is applied through problem-based learning strategies and linking materials to students' daily lives. Character values ​​such as responsibility, honesty, and tolerance grow through real and meaningful learning experiences. This approach has been shown to increase students' awareness and positive attitudes in the practice of religious life. Thus, contextual-based Islamic Studies is an effective medium in shaping students' character.